Playing the white man's tune: inclusion in elite classical music education. Issue 1 (26th March 2020) - Griffiths, Austin
Abstract: This study examined the nature of inclusion for female and black and minority ethnic (BME) young people in elite-level classical music in England. By contrasting the numbers of female and BME students taking part in elite youth orchestras and music schools with the representation of female and BME compositions in the professional classical music repertoire, the study asked whether female and BME inclusion was limited to participation as performers or whether it included adequate representation in terms of the music performed. The survey analysed 4897 pieces from 681 composers drawn from the 2017/18 concert seasons of 10 major English orchestras, 1 week's play lists from two classical music radio broadcasters and the programmes from the last four London Promenade seasons. The study found that female and BME students were well represented in elite music education, but they were very poorly represented in the professional repertoire, where 99% of performed pieces were by white composers and 98% by male composers. Applying Bourdieu's concepts of doxa and illusio, the study concluded that inclusion in classical music in England allowed female and BME musicians to play, but structures in the field maintained a repertoire that continues to be white and male and does not recognise the contributions of female and BME composers. This suggests that inclusion for female and BME musicians is limited and the field continues to promote white and male dominance in its cultural values.